Copper-Catalyzed Carbonylative Coupling of Alkyl Halides - Cheng, Li-Jie; Mankad, Neal P (Accounts of chemical research, 2021)
Conspectus Transition metal-catalyzed carbonylation reactions represent a direct and atom-economical approach to introduce oxygen functionality into organic compounds, with CO acting as an inexpensive and readily available C1 feedstock. Despite the long history of carbonylation catalysis, including many processes that have been industrialized at bulk scale, there remain several challenges to tackle. For example, noble metals such as Pd, Rh, and Ir are typically used as catalysts for carbonylation reactions, rather than earth-abundant alternatives. Additionally, while carbonylation of C(sp2)-hybridized substrates (e.g., aryl halides) is well-known, carbonylation of unactivated alkyl electrophiles, especially where β-hydride elimination can compete with desired CO migratory insertion at the catalyst site, remains challenging for many systems. Recently, base metal catalysis based on Mn, Co, and other metals has enabled advances in carbonylative coupling of alkyl electrophiles, though the nucleophiles are often limited to alcohols or amines to generate esters or amides as products. Thus, we have targeted base metal-catalyzed carbonylative C–C and C–E (E = N, H, Si, B) coupling reactions as a method for approaching diverse carbonyl compounds of synthetic importance. Initially, we designed a heterobimetallic catalyst platform for carbonylative C–C coupling of alkyl halides with arylboronic esters (i.e., carbonylative Suzuki–Miyaura coupling) to generate aryl alkyl ketones. Subsequently, we developed multicomponent carbonylation reactions of alkyl halides using NHC-Cu catalysts (NHC = N-heterocyclic carbene). These reactions operate by radical mechanisms, converting alkyl halides into either acyl radical or acyl halide intermediates that undergo subsequent C–C or C–E coupling at the Cu site. This mechanistic paradigm is relatively novel in the metal-catalyzed carbonylation area, allowing us to discover a previously unexplored chemical space in carbonylative coupling catalysis. We have successfully developed the following reactions: (a) hydrocarbonylative coupling of alkynes with alkyl halides; (b) borocarbonylative coupling of alkynes with alkyl halides; (c) reductive aminocarbonylation of alkyl halides with nitroarenes; (d) reductive carbonylation of alkyl halides; (e) carbonylative silylation of alkyl halides; (f) carbonylative borylation of alkyl halides. These reactions provide a broad range of valuable products including ketones, allylic alcohols, β-borylenones, amides, alcohols, acylsilanes, and acylborons in an efficient manner. Notably, the preparation of some of these products has previously required multistep syntheses, harsh conditions, or specialized reagents. By contrast, the multicomponent coupling platform that we have developed requires only readily available building blocks and rapidly increases molecular complexity in a single synthetic manipulation.